International Olympic Committee consensus statement on youth athletic development. Issue 13 (17th June 2015) - Bergeron, Michael F; Mountjoy, Margo; Armstrong, Neil; Chia, Michael; Côté, Jean; Emery, Carolyn A; Faigenbaum, Avery; Hall, Gary; Kriemler, Susi; Léglise, Michel; Malina, Robert M; Pensgaard, Anne Marte; et al.
Abstract : The health, fitness and other advantages of youth sports participation are well recognised. However, there are considerable challenges for all stakeholders involved—especially youth athletes—in trying to maintain inclusive, sustainable and enjoyable participation and success for all levels of individual athletic achievement. In an effort to advance a more unified, evidence-informed approach to youth athlete development, the IOC critically evaluated the current state of science and practice of youth athlete development and presented recommendations for developing healthy, resilient and capable youth athletes, while providing opportunities for all levels of sport participation and success. The IOC further challenges all youth and other sport governing bodies to embrace and implement these recommended guiding principles.